Deciphering the saccade velocity profile of progressive supranuclear palsy: A sign of latent cerebellar/brainstem dysfunction?. (September 2022) - Terao, Yasuo; Tokushige, Shin-ichi; Inomata-Terada, Satomi; Fukuda, Hideki; Yugeta, Akihiro; Ugawa, Yoshikazu
Highlights: Velocity saccade profile of progressive supranuclear palsy (PSP) showed reduced peak velocity and prolonged duration. The change was most prominent in the cerebellar subtype of PSP and correlated with disease severity. The velocity profile can be used as an indicator of not only brainstem but also cerebellar pathology in various PSP subtypes. Abstract: Objective: To study whether the velocity profile of horizontal saccades could be used as an indicator of brainstem and cerebellar output dysfunction, depending on progressive supranuclear palsy (PSP) subtype. Methods: We compared the velocity profiles in 32 PSP patients of various subtypes with 38 age-matched normal subjects, including Richardson syndrome (RS), PSP-parkinsonism (PSPp), and pure akinesia (PAGF), and cerebellar subtypes of PSP (PSPc). Results: PSP patients showed reduced peak velocity along with increased duration, especially in the deceleration phase. This alteration was more prominent for larger target eccentricities (20–30 degrees), and correlated with disease severity. The changes were most pronounced in PSPc patients, with irregular increases and decreases in velocity profile, followed by RS patients, whereas the change was smaller in PSPp and normal in PAGF patients. Conclusions: Saccade velocity profile can be an indicator of brainstem and/or cerebellar output. Altered velocity profile of PSP patients may reflect the pathology in the brainstem, but may also reflect cerebellar dysfunction, most prominently in PSPc. Significance: Saccade velocity profile may be used as an indicator of latent cerebellar/brainstem dysfunction.